Essential readings in comparative politics - O'Neil, Patrick H (New York: W.W. Norton y Company, 2006)
Contents: What is comparative politcs?. The state. Nations and society. Political economy. authotitarianism and totalitarianism. Democracy. Advanced democracies. Communism and post-communism. Less-developed and newly industrializing countries. Globation. Political violence
Keywords: Comparative Government